Penerapan Model Problem Based Learning Berbantuan Media Digital Storytelling Terhadap Kemampuan Berpikir Kritis - Nadia; Raden Roro Suci Nurdianti; Edi Fitriana Afriza (Lembaga Pengembangan Kinerja Dosen, 2026)
This study was motivated by the low level of students’ critical thinking skills in Economics, resulting from the dominance of conventional teacher-centered instruction. The study aimed to examine the effectiveness of implementing the Problem Based Learning model assisted by Digital Storytelling media in improving students’ critical thinking skills at SMAN 1 Manonjaya. A quantitative approach was employed using a quasi-exprimental method with a non-equivalent control group design. The population consisted of all 216 Grade XI students, while purposive sampling was used to select Class XI G1 as the experimental group and Class XI F2 as the control group. Data were collected through pretest and posttet and analyzed using IBM SPSS Statistics 27. The results showed a significant difference in the improvement of students’ critical thinking skills. The experimental group obtained an N-Gain score of 0,68 (medium category), which was higher than that of the control group (0,41, medium category). Therefore, the implementation of the Problem Based Learning model assisted by Digital Storytelling media proved to be more effective in enhancing students’ critical thinking skills and provides partical implications for instructional in Economics education at SMAN 1 Manonjaya.